The Palaeolithic archaeology of the Almonda karst system (Portugal): a window into half-a-million years of western Iberian prehistory - Zilhão, João (2024)
The spring of the Almonda River is associated with an extensive labyrinth of underground passages whose staggered disposition at different elevations of a 70 m-high escarpment reflects the incision of the region’s hydrographic network. Over the last 500,000 years, the continued lowering of the phreatic level made the outlets associated with these passages available for human use. Eventually concealed by sediment accumulation and roof collapse, such cave entrances have since been rediscovered by systematic spalaeo-archaeological exploration. The ongoing excavation of these localities has shed light on the physical appearance, the stone tool technology, the lifeways, and the palaeoenvironmental background of the regional populations of the Lower, the Middle, and the Upper Palaeolithic. Key finds are the 400,000-year-old cranium from Gruta da Aroeira, which mixes traits previously thought to differentiate the Middle Pleistocene fossils of Europe at the species level, and the evidence for continued, controlled use of fire through the Middle Palaeolithic occupation of Gruta da Oliveira (c. 67.1–107.1 ka). The change through time observed in subsistence economies is parsimoniously explained by demographic increase and an attendant decrease in the size of the territories that individuals roamed across. This trend culminates in the Upper Magdalenian, which sees people focusing on a more limited range of large game and going down the food chain to regularly procure rabbits and river fish.